Analysis of Various IPM Modules Against Pea Leaf Miner (P. horticola G.) Infesting Pea (Pisum sativum L.) - Keval, Ram; H. S., Vanajakshi; Verma, Sunil; Kumar, Abhinav (International Journal of Bio-resource and Stress Management, 2019)
The evaluation of IPM modules under field trial was conducted at Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi during Rabi season of 2016-17 and 2017-18. Experiment was conducted by using high yielding cultivar HUDP- 15, with five IPM modules and three replication in randomized block design, the study revealed that the population of pea leaf miner persisted in the field from 2nd to 11th standard week. When the overall mean of the per cent leaf infestation by P. horticola was considered together, the minimum per cent infestation (13.72%) was observed in module 2 followed by module 4 (19.22%), and the highest infestation were observed in module 3 (54.54%) over the untreated control (40.41%) during 2016-17. Similarly, in the year 2017-18, the minimum per cent leaf infestation was found in module 2 (11.20%) followed by module 1 (15.70%) and the highest infestation were observed in module 3 (17.20%) over the untreated control (module 5). The highest cost: benefit ratio found in module 1 (1:7.3) followed by module 4 (1:5.9) and lowest in module 2(1:3.2) during the year 2016-17. Similarly during the year 2017–18 the highest C:B ratio was found in module 1 (1:8.5) followed by module module 4 (1:4.5) and least in module 2 (1:3.9), module 1 is both effective as well as economical, and hence it can be recommended to farmers.